Dementia across local districts in England 2014 to 2015. (4th June 2018) - Tampubolon, Gindo; Nazroo, James; Keady, John; Pendleton, Neil
Abstract : Background: The number of older people needing dementia care is projected to rise rapidly, and local districts are now charged with responding to this need. But evidence on local area factors of dementia is scarce. We studied the odds of dementia prevalence and its individual risk factors enriched with area factors. Materials and methods: This study analysed objectively assigned dementia prevalence in people aged 60 and over living in community in England, drawing data from the English Longitudinal Study of Ageing 2014 to 2015 and local districts statistics using multilevel logistic models. Dementia status is ascertained using a modified version of the Telephone Interview for Cognitive Status. A number of individual risk factors were considered including social determinants, internet use, social connections, and health behaviours; 2 contextual factors were included: the index of multiple deprivation and land use mix. Results: The prevalence of dementia by this method is 8.8% (95% confidence interval 7.7%‐9.2%) in older adults in England. Maps of dementia prevalence across districts showed prevalent areas. In the full model, no area characteristics were significant in predicting dementia prevalence. Education, social connections, internet use, and moderate to vigorous physical activity showed protective associations. Conclusion: Dementia in older adults in England is largely predicted by individual characteristics, although some districts have a large share of their population with dementia. Given the health and social care costs associated with dementia, differential interventions and support to districts and to groups of individuals defined by these characteristics seem warranted.